2019
DOI: 10.1002/ecs2.2711
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the effects of climate variability on waterbodies and wetland‐dependent birds in the Prairie Pothole Region

Abstract: Understanding how bird populations respond to changes in waterbody availability in the climatically variable Prairie Pothole Region (PPR) of North America hinges on being able to couple hydrological and climate modeling to represent potential future landscapes. Model experiments run with the Pothole Complex Hydrologic Model using downscaled climate data (variables relating to precipitation, temperature, and potential evapotranspiration at 1/8° spatial resolution under four general circulation climate models an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 69 publications
2
13
1
Order By: Relevance
“…2016, McIntyre et al. 2019) and are in contrast to other studies that have suggested a large, southeastern shift in viable waterfowl habitat in the PPR (Johnson et al. 2005, Johnson and Poiani 2016).…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…2016, McIntyre et al. 2019) and are in contrast to other studies that have suggested a large, southeastern shift in viable waterfowl habitat in the PPR (Johnson et al. 2005, Johnson and Poiani 2016).…”
Section: Discussioncontrasting
confidence: 65%
“…Additionally, multiple wetland monitoring efforts have been sustained for over three decades and enabled the development of different modeling tools and approaches to assess how climate change could impact wetlands and waterbirds in the PPR (Johnson and Poiani 2016, McIntyre et al. 2019, McKenna et al. 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect can be seen in Figure 8, where the wetland area remains very elevated across years of varied climate in the drained scenario as compared to the undrained scenarios. Extreme precipitation events are projected to increase under climate change in the PPR [83], and our findings suggest these larger events can have multi-decadal hydrological impacts that are greatly magnified when extensive consolidation exists on the landscape.…”
Section: Discussionmentioning
confidence: 70%
“…Projected climate-model means under moderate increases in emissions from Representative Concentration Pathway (RCP) 4.5 project precipitation for the Northern Great Plains region could increase by as much as 10% or decrease by as much as 5% from historical levels (USGRCP 2017). The potential impact of future climate change on prairie-pothole wetlands ranges between wetlands being much drier (Johnson et al 2010) or moderately wetter (McIntyre et al 2019) in the future. Upland management practices may help maintain ponded water important to breeding waterbirds.…”
Section: Introductionmentioning
confidence: 99%